Mathematical Model Analysis of the Impact of Alcohol Consumption on the Dynamics of Poverty and Infectious Disease - Kiros G. Kebedow; Tesema M. Mune; Mohammed Y. Dawed (Journal of Applied Mathematics)
Alcohol consumption causes social, economic, and health concerns. Our proposed mathematical model examines how alcohol intake affects the dynamics of infection and poverty. This study looks at two types of infectious diseases as well as poverty dynamics caused by alcoholism. The model’s dynamic behavior is evaluated qualitatively. The system has three equilibrium points: disease free, alcohol free, and endemic. The existence of these points is explained as follows: no condition, a condition, and conditions. Two fundamental reproduction numbers are identified. The current model system has demonstrated theorems on local and global fixed point stability analysis with proofs. Extensive numerical simulation has been carried out using the MATLAB ODE solver Ode45 which reveals the validity of qualitative analysis of the dynamical system.